Effect of coupling in steel/aluminium laminate subjected to tensile load - Ang, Dionysius Wei Qian (Nanyang Technological University, 2021)
This project involves the study of coupling effects in steel/aluminium laminated structure when subjected to tensile loading. Three different cases of laminated structure are modelled and analysed using ANSYS. In the first case, the number of layers of constituent metals is increased while other aspects of the structure remain constant. In the second case, the aspect ratio of the laminated composite is changed from a cantilever plate to a cantilever beam while the number of layers of the constituent metals remains at two. In the third case, the volume percentage of the constituent metals is varied while the aspect ratio and the number of layers remain constant. Finite element modelling (FEM) was used to obtain the results in this report. The load was applied at the tip of a cantilever structure, with a thickness of 2.72mm, a length of 500mm, and a width of 200mm. The width was varied in the second case to change the aspect ratio of the structure. The results for the first case show lesser bending-extension coupling effect when the number of layers is increased. In the second case, the results show that flexural stiffness increases as the structure is modified from a cantilever sheet to a cantilever beam and the structure shows lesser bending-extension coupling effect. In the third case, the results show that there is a point of low flexural stiffness when aluminium takes up 60% of the volume proportion of the structure and hence, a point with the highest bending-extension couple effect.